THE ESSENCE OF INTERCULTURAL SKILLS IN LEARNING A FOREIGN LANGUAGE - Tadjibaeva Adila Ergashevna (Bright Mind Publishing, 2025)
In today’s globalized world, learning a foreign language goes beyond mastering grammar and vocabulary—it requires the development of intercultural skills. This article explores the essence of intercultural competence as a core element in foreign language acquisition. It emphasizes how the ability to understand, respect, and interact effectively with people from diverse cultural backgrounds enhances both linguistic performance and communication effectiveness. Drawing on contemporary pedagogical theories and case studies, the study highlights the integration of cultural content into language curricula, the role of educators in modeling intercultural sensitivity, and the importance of reflective learning. The findings suggest that learners who actively engage in intercultural experiences show greater motivation, adaptability, and communicative competence. The paper concludes by proposing practical strategies to embed intercultural education into foreign language teaching frameworks, thereby fostering global citizenship and cross-cultural understanding.
Keywords: Intercultural competence, foreign language learning, cultural awareness, global communication, language pedagogy, cross-cultural education, communicative competence.